2010
DOI: 10.1016/j.virol.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The polyomavirus BK agnoprotein co-localizes with lipid droplets

Abstract: Agnoprotein encoded by human polyomavirus BK (BKV) is a late cytoplasmic protein of 66 amino acids (aa) of unknown function. Immunofluorescence microscopy revealed a fine granular and a vesicular distribution in donut-like structures. Using BKV(Dunlop)-infected or agnoprotein-transfected cells, we investigated agnoprotein co-localization with subcellular structures. We found that agnoprotein co-localizes with lipid droplets (LD) in primary human renal tubular epithelial cells as well as in other cells supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…First, immunofluorescent staining of SVG p12 cells with antiserum directed against BKPyV agnoprotein, previously shown not to cross-react with SV40 or JCPyV agnoprotein, showed the characteristic cytoplasmic staining pattern seen in BKPyV-infected cells (45,57). This result was confirmed in a separate laboratory and by Western blotting.…”
Section: Discussionmentioning
confidence: 55%
“…First, immunofluorescent staining of SVG p12 cells with antiserum directed against BKPyV agnoprotein, previously shown not to cross-react with SV40 or JCPyV agnoprotein, showed the characteristic cytoplasmic staining pattern seen in BKPyV-infected cells (45,57). This result was confirmed in a separate laboratory and by Western blotting.…”
Section: Discussionmentioning
confidence: 55%
“…It is also interesting to note that all three Phe residues of agnoprotein (Phe31, Phe35, and Phe39) localize to its hydrophobic region. The functional importance of these Phe residues has recently been evaluated by genetic and biochemical approaches, and it was demonstrated that they positively influence viral DNA replication (1,4) and play regulatory roles in the perinuclear distribution of agnoprotein in infected cells (4,5). Agnoprotein possesses only one highly conserved Cys residue, which is located right after the hydrophobic region of the protein (Cys40).…”
mentioning
confidence: 99%
“…However, two major required features of amino acid sequence have been proposed: one is the amphipathic ␣ -helix (19)(20)(21)(22)(23), and the other is a rather undefi ned hydrophobic region (24)(25)(26). Some LD-targeting proteins, such as caveolin-1 and associated with lipid droplet protein 1 (ALDI) ( 24,42 ), showed dual localization to LDs and ER in relation with cellular lipid dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Although several cellular and viral proteins localize on the LD membrane, consensus signals for LD targeting are not defi ned ( 1 ). Recent reports have shown that LD-targeting activity resides in amphipathic helices (19)(20)(21)(22)(23) or in hydrophobic regions (24)(25)(26).…”
Section: Immunofl Uorescencementioning
confidence: 99%
See 1 more Smart Citation